Analisis Bahaya Fisik: Hubungan Tingkat Pencahayaan dan Keluhan Mata Pekerja pada Area Perkantoran Health, Safety, and Environmental (HSE) PT. Pertamina RU VI Balongan - Dina Rahmayanti; Angela Artha (Jurnal Optimasi Sistem Industri, 2015)
The eyes are part of the body that must be protected workers safety and health. Sufficient light is one of the most important aspects that determine the health of the eye, excellent lighting intensity affects the eyes. This study was performed at PT Pertamina RU VI Balongan, based on observation in the work area, it is necessary to evaluate the intensity of light and eye strain workers in a unit of PT. Pertamina Refinery Unit VI Balongan.Be collected from primary and secondary data and processing in the form of statistical testing using Microsoft Excel and SPSS Software 2.0. Tests conducted on four types of questionnaires and data variables intensity lighting in the office area of HSE unit RU VI Balongan.There are 12 rooms which have the following illumination standard (under 300 lux). Based on a statistical test between the variable quality of the lighting of the eye complaints get results there are two variables that have a relationship. In addition, all respondents had complaints of eye fatigue that varies with the highest percentage of 80% with complaints of eye feel sleepy and 63% of workers feel pain in the neck or shoulder.